Permasalahan Guru dalam Perspektif Manajemen SDM Pendidikan Islam: Tantangan dan Solusi - Zahara, Sri; Oktavia, Lidya Fransiska; Yovica, Alia; Refnawati, Refnawati; Yuliani, Tri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article aims to analyze teacher problems in the perspective of Islamic education human resource management. This article uses the methodology of literature study to explore the various challenges faced by teachers in the context of human resource management of Islamic education. Databases such as Google Scholar are used to search for relevant sources of study, with search terms including